Improving the efficiency of Hale & Co Builders’ Merchant - Mani, Pravinkumar (2013)
The purpose of this thesis is to suggest recommendations that will improve the overall efficiency of the company Hale & Co, a builder’s merchant in Forest of Dean, Gloucestershire. It primarily was focused to check the effect of pre-picking in the yard and if it will be effective enough if the goods were pre-picked before collection for delivery. A detailed site visit was arranged to collect the information and to understand the current practices followed by the company. In the attempt to collect information interviews were conducted with staff at different levels, time measurements were done and the varied ways of improving the warehouse performance were realized through detailed literature review. Data analysis indicated that pre-picking will not be satisfactorily effective to increase the picking efficiency in the yard. The other recommendations include making minor changes such as using a warehouse management system to help allocating the orders to the trucks, sequencing the orders for picking, changing the current order receipt collection process, making separate paths for material handling equipment, introducing direction sign posts, improving the location accuracy by implementing RFID tags which will also give a better inventory control. The thesis concludes by suggesting what are the recommendations that can be implemented on a long and short run. There is scope for future work where the pre-picking efficiency can be analyzed by simulating the current set of practices and checking for different scenarios.